Analisis Kepuasan Konsumen di UMKM Ayam Geprek Sriwedari - Rangga Rangga; Uus Mohammad Darul Fadli (Jurnal Manajemen Bisnis Digital Terkini, 2024)
This research aims to conduct an analysis of consumer satisfaction at Ayam Geprek Sriwedari MSMEs. This research involved 100 respondents who were consumers of the restaurant. This study focuses on five indicators, namely product quality, service quality, emotional aspects, product price and costs. The research results show that overall the five indicators received a good positive response from consumers. These findings indicate that the factors studied have a significant contribution to consumer satisfaction with Ayam Geprek Sriwedari. The implications of this research suggest the need for MSMEs to continue to improve and maintain product quality, service, emotional aspects, product prices, and manage costs well in order to maintain consumer satisfaction and increase business competitiveness. This research provides valuable insight for MSME managers in understanding the factors that are important in creating positive experiences for consumers and strengthening market share.